Maximizing specific work output extracted from engine exhaust with novel inverted Brayton cycles over a large range of operating conditions. (15th January 2020) - Chagnon-Lessard, Noémie; Copeland, Colin; Mathieu-Potvin, François; Gosselin, Louis
Abstract: The heat contained in internal combustion engine exhaust gases can be converted into mechanical energy by using an Inverted Brayton Cycle (IBC). In this paper, five different IBC versions are numerically modeled and optimized to maximize their specific work output: (i) basic IBC, (ii) IBC with liquid water drainage (IBC/D), (iii) IBC with liquid water drainage and a steam turbine (IBC/D/S), (iv) IBC with liquid water drainage and a refrigeration cycle (IBC/D/R), and (v) IBC with liquid water drainage, a steam turbine and a refrigeration cycle (IBC/D/S/R). The three latter cycles are presented for the first time in literature. The optimization is performed for a wide range of inlet gases temperatures (600–1200 K) and heat sink temperatures (280–340 K). Among the five IBCs, the IBC/D/S/R has the highest specific work output for the whole range of operating temperatures. A comparison with the subcritical Rankine cycle and Organic Rankine Cycles using isobutane and benzene shows that an IBC system might be a better choice for specific operating temperatures. Liquid water addition in the IBC/D/S/R leads to optimized designs using only the steam turbine at high inlet gas temperatures, indicating that a Rankine cycle is better suited for these conditions. Highlights: The inverted Brayton cycle is a good candidate for heat recovery from exhaust gases. It is best combined with water drainage, vapor-compression and open Rankine cycles. Work output of 270 kJ per kg of exhaust at 1200 K can be reached with 280 K cold sink. It outperforms ORC and Rankine cycle for certain hot and cold source temperatures.